2013
DOI: 10.1063/1.4853035
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of carrier behavior in C60/P(VDF-TrFE) double-layer capacitor by using electric-field-induced optical second-harmonic generation measurement

Abstract: By using displacement current measurement (DCM) and electric-field-induced optical second-harmonic generation (EFISHG) measurement, we studied the carrier behavior in the indium-tin oxide (ITO)/Poly(vinylidene fluoride-trifluoroethylene) (P(VDF-TrFE))/C60/Au(or Al) capacitors. Two DCM peaks appeared asymmetrically at around −35.5 V and +30.0 V in the dark. Correspondingly, the EFISHG response from the C60 layer was observed, but the peak positions were different with respect to DCM ones. The results show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
(63 reference statements)
0
8
0
Order By: Relevance
“…As a result, the SH intensity in the BHJ layer is generated in proportion to jE b þ E e (t)j 2 , where E e (t) ¼ (V ex /d)(1-exp(-t/t RC )). [7][8][9]12 Here, d is the thickness of BHJ layer, and t RC is the circuit response time that can be given by t RC ¼ RC (R is the series The decrease or increase in the electric field in the BHJ layer depends on the polarity of the "E b ". Results given in Figure 5(a) show that the electric fields "E b1 " in PCDTBT and "E b2 " in PC 71 BM are pointing in the direction from ITO to Al electrode.…”
Section: B Efishg Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the SH intensity in the BHJ layer is generated in proportion to jE b þ E e (t)j 2 , where E e (t) ¼ (V ex /d)(1-exp(-t/t RC )). [7][8][9]12 Here, d is the thickness of BHJ layer, and t RC is the circuit response time that can be given by t RC ¼ RC (R is the series The decrease or increase in the electric field in the BHJ layer depends on the polarity of the "E b ". Results given in Figure 5(a) show that the electric fields "E b1 " in PCDTBT and "E b2 " in PC 71 BM are pointing in the direction from ITO to Al electrode.…”
Section: B Efishg Measurementmentioning
confidence: 99%
“…Here,Ẽ b is formed due to work function difference of the electrodes, whereasẼ ext andẼ sc are mainly formed under voltage application. [7][8][9] In the presence of local electric field Eð0Þ, the EFISHG is activated. During the EFISHG measurements, we used red light (660 nm wavelength, 10 Hz repetition, 50 ms duration) emitted from a laser diode to induce photo current.…”
Section: B Efishg Measurementmentioning
confidence: 99%
“…These studies are mainly carried out by means of electrical measurements such as displacement current measurement (DCM) using ramp voltage [150,151], but these are no longer sufficient to account for carrier behaviors in a variety of organic semiconductor devices being utilized with ferroelectric P(VDF-TrFE) layers. Using EFISHG probes the electric field change induced in organic devices with a ferro-electric layer gives much information on the carrier behavior in these devices [152][153][154]. Figure 16 shows a typical example of DCM measurements for MFM and MFSM (the inset of Fig.…”
Section: A Double Layer El Diodesmentioning
confidence: 99%
“…layers. Using the EFISHG measurement is an effective way for clarifying the contribution of organic semiconductor layers [153,155].…”
Section: A Double Layer El Diodesmentioning
confidence: 99%
“…In our previous paper, we studied the displacement current-voltage characteristics of metal/ ferroelectric/ organic semiconductor/ metal (MFS) diodes by using the EFISHG measurement [26]. Results showed that the EFISHG measurement coupled with displacement current measurement (DCM) is useful for analyzing the relationship between the polarization reversal process in the ferroelectric layer and associated carrier behaviors in the semiconductor layer, in terms of the three-peak generation in the DCM [27][28][29]. We also used the charge modulation spectroscopy (CMS) to study the relationship between the related energetics of carriers in semiconductor layer and polarization reversal in MFS diodes [26].…”
Section: Introductionmentioning
confidence: 99%